IMPACT OF GRAPE SEEDS EXTRACT AGAINST ALLOXAN INDUCED DIABETES IN MICE - Ahmed H. M.; A. C. Saddam (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The current study was aimed to evaluate the antidiabetic effect of grape seed extract (GSE) on Alloxan (120mg/kg of body weight) induced diabetes in mice as well as characterize the chemical composition and phytochemical content of grape seeds from three grape cultivars (Ahmer, Halawani, and Kamali) grown in Iraq as well as pomace. Ahmer gave the highest values for crude fat14.84±0.2 and phytochemicals (tannins, saponin, alkaloids, flavonoids, phenol, and anthocyanin) as compared to other cultivars. phytochemical analysis using High-performance liquid chromatography (HPLC) revealed that the highest concentration of proanthocyanidins polymers (catechine, procyanidin, and epicatechine) was recorded in Ahmer seed extract which were (796, 170, 244) µg/g, respectively, while the lowest amounts were in pomace 489, 99, and 143 µg/g, respectively using HPLC. Oral administration of grape seed natural extract (600 mg/kg/day) reduced the level of glucose in mice which was highly statistically significant (p <0.01) compared with the diabetic control mice (untreated), which was 206.83±6.7 and 349±27.50 mg/dl, respectively.